PENGARUH FASILITAS KERJA, KOMPETENSI DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI CV. LANGIT SORE INDONESIA KABUPATEN BANGKALAN - Mayangsari, Linda Dwi (Universitas Nusantara PGRI Kediri, 2023)
The background of this research is that there are facilities in an organization or company that need to be improved in order to improve the performance or work performance of its employees. In order for the company to achieve the aims and objectives of the company's goals that have been formulated, the company must pay attention to the factors that affect the work performance of its employees, both in the form of work facilities, competence and motivation, so that the company's goals are achieved and employees are increasingly improving their work performance. The purpose of this study was to determine the effect of work facilities, competencies, and motivation on employee performance at CV. Langit Sore Indonesia Bangkalan. This research uses a quantitative approach with descriptive quantitative. The sample used in this study included 33 employees of CV. Langit Sore Indonesia Bangkalan and analyzed using multiple linear regression with SPSS software for windows version 26. The conclusions of the results of this study are (1) work facilities do not affect the work performance of employees CV. Langit Sore Indonesia Bangkalan. This can be seen from the results of the t test that the significance value of the work facility variable is 0.855 > 0.05 and tcount: 0.184 <2.048. (2) Competence has no effect on the work performance of employees CV. Langit Sore Indonesia Bangkalan. 3) Work motivation has no effect on work performance of employees in CV. Langit Sore Indonesia Bangkalan. (4) work facilities, competence and work motivation together have an influence on the work performance of employees in CV. Bangkalan Indonesian Evening Sky.